Nicaea and its legacy: an approach to fourth-century Trinitarian theology - Ayres, Lewis (Oxford University Press, 2004)
Lewis Ayres offers a new account of the relevance of Nicene trinitarianism for modern theology. He emphasizes the spiritual and contemplative life that accompanies thinking about the Trinity